IDENTIFIKASI STATUS KIMIA TANAH PADA LAHAN TANAMAN KARET DI DESA TUNGGAL BHAKTI : IDENTIFIKASI STATUS KIMIA TANAH PADA LAHAN TANAMAN KARET DI DESA TUNGGAL BHAKTI - leony agustine; Andri Andri (LPPM UNIVERSITAS KAHURIPAN KEDIRI, 2024)
Rubber plantations can grow and produce high quality results if they are cultivated in a suitable environment. Efforts to support land suitable for use in rubber cultivation include identifying the chemical status to determine the level of soil fertility. Tunggal Bhakti Village is one of the villages that has the potential to cultivate rubber plantations for the community. The lack of information known by farmers about the status of soil fertility and land management actions has resulted in less than optimal rubber productivity. The aim of this research is to identify the soil chemical status of rubber plantations in Tunggal Bhakti Village, Kembayan District, Sanggau Regency. This research was carried out using the method used in this research, namely the survey method according to land map units (SPT) and there were 2 SPTs at the research location. Taking composite soil samples to analyze the chemical properties of the soil, 1 kg of composite soil samples were taken at a depth of 0-30 cm and 30-60 cm at each SPT for analysis in the laboratory. Criteria for assessing soil chemical properties were identified based on Soil Research Center Staff (1993). The research results show that soil fertility in terms of its chemical properties is classified as low to very low.